Pesantren dan Globalisasi - Astuti, Sri Andri (Tarbawiyah Jurnal Ilmiah Pendidikan, 2014)
From era to era, generation to generation, the role of islamic boarding house by fucntion and task of islamic scholar and their religious pupil is to fighting to construct the religious values and also defense of islam for transforming the growth and develop the society. The objectives which discuss is for the life of society in balancing condition between wold and here after aspect. Based on the sistemik and religi approach have acknowledge that the function of islamic boarding house have to support students individual to build social group who have strong potential to fiil in the build of this country. By that the conception, islamic boarding house is ideal course, because of in islamic boarding house have concept of education which are integralistics, pragmatics and have culture root in environment society.